Religion, Culture and Local Wisdom in the Death Ritual of Pontianak Malay Society - Sumarman Muhammad Djar’ie; Zaenuddin Hudi Prasojo (Graduate Program of Pontianak Institute of Islamic Studies, 2015)
Death is inevitable and will occur to every living creature, including humans no mater what religion or belief they have; however, no one knows for sure when it happens. Humans can only predict death based on indicators that can be seen before it occurs. Still until now, there are many people who attempt to oppose death, even though in the end they have to admit that Allah is the Almighty. Therefore, no wonder if the death is still considered a tragedy rather than the culmination of happiness when humans finally harvest of deeds they have done all their life. In this light, death rituals are often accompanied by the tears of the family of the deceased, even some cry hard to express their pain as someone they love is gone, coupled with the arrival of relatives and acquaintances who mourn, and condolences as well as the phrase “inna lillâh wa inna ilaihi raji’ȗn”. A day of joy has turned into a day of sorrow, although it always ends with kendurian (gathering for remembering the dead), whose excitement is like that of selamatan (communal feast) and syukuran (celebration of thankfulness). This paper tries to present the infiltration of religion and culture in the death ritual in Pontianak Malay community as an object of discussion of local wisdom by using mafhȗm mukhâlafah approach, to provide a new understanding of the meaning of death.